Gaya Penceritaan Leila S. Chudori dalam Novel Laut Bercerita - Julianto, Ecandra; Hiasa, Fina; Chanafiah, Yayah (UNIB Press, 2025)
The purpose of this research is to examine the narrative style of Leila S. Chudori in the novel Laut Bercerita. The research employs a qualitative method with a stylistic approach. Data collection techniques used include literature review. The data analysis technique in this study involves: (1) collecting references that can serve as a basis for the research; (2) reading and understanding the novel Laut Bercerita by Leila S. Chudori, as well as creating a synopsis of the novel; (3) gathering data related to the narrative style of Leila S. Chudori in her work; (4) categorizing the data that pertains to the narrative style; (5) identifying the collected data and analyzing the narrative style of Leila S. Chudori in her work; and (6) drawing conclusions. The research findings indicate that the narrative style in the novel Laut Bercerita by Leila S. Chudori is characterized by the use of the first-person point of view with two main characters from different generations. The author employs various language styles such as personification, sarcasm, hyperbole, simile, and metaphor for comparison and satire. Character portrayal is carried out through analytical and dramatic techniques. The setting of the novel includes (a) place; (b) time; (c) atmosphere. From this, it is evident that Leila S. Chudori's narrative style in Laut Bercerita combines history and fiction with distinctive features of a bold narrative style that includes humor, sarcasm, vulgar (frontal) language, presents the realities of the time, and tends to be critical of the government, serving as a social and political critique.